1982
DOI: 10.7164/antibiotics.35.680
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid biosynthesis of derivatives of protylonolide and M-4365 by macrolide-producing microorganisms.

Abstract: Biotransformation of a macrolide antibiotic and a related compound was studied using various macrolide-producing microorganisms grown in the presence of cerulenin, an inhibitor of de novo synthesis of the aglycone moiety. Protylonolide (1) was transformed into 5-0-(4'-O-propionylmycarosyl)protylonolide (2) by a leucomycin-producing strain, Streptoverticillium kitasatoensis KA-429. M-4365 G2 (3) was bioconverted into M-4365 G3 (4), 9-dihydro M-4365 G3 (5), 3-O-acetyl M-4365 G3 (6) and 3-O-acetyl-9-dihydro M-436… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Production of novel antibiotics by mutasynthesis (15) or hybrid biosynthesis (10,11,13) is an interesting approach to the discovery of new antibiotics. Such methods are easily applied to obtain new antibiotics, but their fermentations need at least two processes: (i) cultivation of an idiotrophic mutant or an antibiotic-producing strain by the addition of an enzyme inhibitor and (ii) the addition of an analog of a biosynthetic intermediate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of novel antibiotics by mutasynthesis (15) or hybrid biosynthesis (10,11,13) is an interesting approach to the discovery of new antibiotics. Such methods are easily applied to obtain new antibiotics, but their fermentations need at least two processes: (i) cultivation of an idiotrophic mutant or an antibiotic-producing strain by the addition of an enzyme inhibitor and (ii) the addition of an analog of a biosynthetic intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…These include mutasynthesis (15), in which an unnatural precursor is fed to an idiotroph genetically blocked in antibiotic biosynthesis, and hybrid biosynthesis (10,11,13), in which a wild-type strain is fed with such a precursor in the presence of an enzyme inhibitor which phenotypically blocks the biosynthetic pathway of the recipient strain. Another approach to the production of novel antibiotics is interspecific mating (9,14) or protoplast fusion (4,5).…”
mentioning
confidence: 99%
“…Figure 37 shows the biosynthesis of nanaomycin and the site of action of cerulenin. Taking advantage of this mechanism of action, we have obtained a number of hybrid antibiotics (80,99,100).…”
Section: Basic and Applied Researchmentioning
confidence: 99%
“…It displays fair and broad-spectrum antibacterial properties, although it is more potent against gram-positive pathogens [3]. There have been some reports regarding the microbial biotransformation of this antibiotic [1,2,5,6,11]. Supplementation of the chemically de-epoxidized aglycone of rosamicin into a randomly mutated strain of mycinamicin-producing Micromonospora polytrota provided new derivatives of rosamicin, such as mycinosyl deoxysugar-attached rosamicins [6].…”
mentioning
confidence: 99%
“…Recent studies have reported that the above mycinosyl rosamicin derivative could be produced by a genetically engineered recombinant of M. rosaria in which the gene set responsible for the biosynthesis and attachment of mycinose was introduced [1,2,5]. In addition, structural modification of a biosynthetic precursor of rosamicin, M-4365 G2, using various macrolide-producing microorganisms has been reported, with attachment of the acetyl group at the C3 hydroxyl position and reduction of the carbonyl function at the C9 position [11]. However, none of the above-described rosamicin analogs exhibited higher antibacterial activity than the parent rosamicin.…”
mentioning
confidence: 99%